A new method for job scheduling in two-levels hierarchical systems - Shokripour, Amin; Othman, Mohamed; Ibrahim, Hamidah; Subramaniam, Shamala (Springer Berlin Heidelberg (SpringerLink), 2013)
The use of parallel and distributed systems has become very common in the last decade. Dividing data is one of the challenges in these types of systems. Divisible load theory (DLT) is one of the proposed methods for scheduling data distribution in parallel or distributed systems. Many researches have been done in this field, but scheduling a multi-installment heterogeneous system with two-level hierarchical topology in which communication mode is blocking has not been addressed. In this paper, we find the proper size of task for each sub tree. Finally, in the experiments section, we show that the proposed methods work correctly and give us the best scheduling